Study of performance and management practices of Dumba sheep in semi-arid region of the India - AK Mishra,; A Jain,; S Singh,; KS Rathore, (Journal of Livestock Biodiversity, 2025)
Characterization and performance evaluation of fat –tailed Dumba sheep was undertaken through survey in Jaipur, Nagaur and Ajmer districts of Rajasthan. The data on body biometry, phenotypic characters and other performance traits were collected through measurements, personal observations and information provided by the sheep farmers. Dumba animals are large in size which is also relected by its body weight and body biometry. The coat colour is white, brown, white with brown patches and white with black patches all over the body. The predominant colour is white (43.86%), followed by brown or mixture of white and brown (41.23%) and black-white mixture (14.91%). Ears are large, pendulous and drooping. Ear length ranged from 9 to 26 cm. Legs, face and belly are devoid of wool. Head is slightly convex in majority of animals (62.02%). Muzzle is pink and hooves are light brown or grey in colour. Both the sexes are polled, however, horns were observed in some of the males. The price of Dumba animals is very high as claimed by sheep owners. Adult animals are sold at the rate of Rs 60000 to 125000 and lambs @ Rs 25000-40000. The average lock size was 16.04.  The average adult body weight of rams and ewes were 83.89 ± 3.95 and 58.76 ± 1.79 kg, respectively which ranged from 50 to 124 kg in rams and 35 to 96 kg in ewes. The overall body length, height, chest girth, paunch girth, face length, face width, ear length and tail length were 71.88 ± 0.55, 76.07 ± 0.60, 93.38 ± 0.79, 94.78 ± 0.85, 20.86 ± 0.18, 9.59 ± 0.08 and 17.69 ± 0.22 cm respectively. Body weight of lambs in the age groups of 1-3 and 3-6 months ranged between 11-32 and 20 -60 kg respectively. Animals are maintained under intensive or semi-intensive system of management with no grazing.  Dumba sheep is maintained primarily for sacri ice (qurbani) or earn handsome money from sale during the Bakr-Eid festival. Dumba sheep, on account of its demand for the religious ritual, is contributing to the livelihood of sheep farmers.